2022
DOI: 10.1021/acs.jpcc.2c01753
|View full text |Cite
|
Sign up to set email alerts
|

Gradually Fe-Doped Co3O4 Nanoparticles in 2-Propanol and Water Oxidation Catalysis with Single Laser Pulse Resolution

Abstract: Controlling the surface composition of colloidal nanoparticles is still a challenging yet mandatory prerequisite in catalytic studies to investigate composition-activity trends, active sites, and reaction mechanisms without superposition of particle size or morphology effects. Laser post-processing of colloidal nanoparticles has been employed previously to create defects in oxide nanoparticles, while the possibility of laser-based cation doping of colloidal nanoparticles without affecting their size remains mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Hence, nanosecond-pulsed UV laser excitation of nanoparticles in the low fluence regime applied here is most likely linked to a particle-surface-heating process, causing pulsed-laser-induced diffusion enhancement. 17 Furthermore, ion uptake specificity (higher affinity of Fe than Cu as found in 18 ) seems to be less pronounced (not dominant) at lower doping levels or in case no size reduction occurs. Upon co-doping with Sr, the Fe doping levels drastically increased by a factor of 9, so the presence of Sr seemed to promote Fe doping.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, nanosecond-pulsed UV laser excitation of nanoparticles in the low fluence regime applied here is most likely linked to a particle-surface-heating process, causing pulsed-laser-induced diffusion enhancement. 17 Furthermore, ion uptake specificity (higher affinity of Fe than Cu as found in 18 ) seems to be less pronounced (not dominant) at lower doping levels or in case no size reduction occurs. Upon co-doping with Sr, the Fe doping levels drastically increased by a factor of 9, so the presence of Sr seemed to promote Fe doping.…”
Section: Resultsmentioning
confidence: 98%
“…16 Recently Zerebecki et al reported laser-induced doping of Fe ions into Co 3 O 4 by applying low fluence laser heating and precisely controlling the number of laser pulsed per colloid volume. 17 Laser-based doping of bioactive glass (BG) on the other hand has been rarely explored. In one study Li and Ramesh et al examined the reactive laser fragmentation of micrometer-sized 45S5 BG in the presence of Cu (EDTA) and Fe (EDTA) complex solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we gained mechanistic insight into the LFL process of organic molecules, postulating a simultaneous contribution of multiple fragmentation mechanisms based on the stress confinement criterion, a degradation‐free ablation enabled by residual water, as well as the formation of an internal quasi‐stationary stress gradient within MP, prone to stimulate further fundamental research in this area. Here, particularly a newly developed flat‐jet passage reactor, which was demonstrated to enable a more homogeneous illumination and more precise pulse per volume control in metal [ 58 ] or oxide [ 59 ] nanoparticle pulsed laser excitation, could be a useful asset to further clarify the fragmentation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Laser fragmentation in liquids fills this gap by providing monodisperse, surfactant-free, colloidal sub-5 nm particles . Additionally, particularly for transition metal oxide nanoparticles, changes in the oxidation state and cation occupancy of tetrahedral and octahedral sites with the number of laser pulses and even laser-induced cation doping have been shown in the past. Hereby, both oxidation and reduction , reactions, mostly located in surface-near particle layers, were observed to occur with ongoing laser irradiation, with the oxidation/reduction tendency appearing to correlate with the initial oxidation state and redox potential of the initial particles.…”
Section: Introductionmentioning
confidence: 99%